Pathways to industrialization in the twenty-first century : new challenges and emerging paradigms - Szirmai, Adam, Ed (Oxford University Press, 2017)
This text deals with the importance of industrialization and the development of manufacturing in the economic development process. It focuses specifically on new challenges such as global value chains, the rise of China, climate change, and the role of state versus private sector entrepreneurs in forging appropriate industrial policies.